Korelasi Penguasaan Kosakata dengan Keterampilan Berbicara Siswa dalam Bahasa Inggris - Adhityo Kuncoro (Universitas Indraprasta PGRI Jakarta, 2017)
The purpose of this research is to scientifically show a correlation between vocabulary mastery and speaking skill. The research, using a survey method, is performed in three classes of first semester students at Universitas Indraprasta PGRI, with 40 respondents taken from students of two different classes. The data of the research are obtained through written tests, then processed using SPSS 2.0 program and analyzed applying regression and correlation analyses. The result of the research shows a significant effect of vocabulary mastery on speaking skill as seen by the value of sig=0,000 (sig<0,05) and tobserved = 3,694 (tobserved is more than ttable= 1,69). Based on the result of the research, it can be concluded that vocabulary mastery has an effect on or a correlation with student’s speaking skill.